THE EFFECT OF FLASHCARD MEDIA AND THE LITERACY WINDOW ON STUDENT VOCABULARY MASTERY AT SMP ISLAM TERPADU AL-WAHIDIYAH - Sulistiawati, Marni; Yassin, Muhammad (PENA KREATIF : JURNAL PENDIDIKAN, 2026)
Vocabulary plays a central role in English learning because it enables students to understand texts and express ideas effectively. However, many junior EFL students still face difficulties in mastering vocabulary due to limited exposure and low motivation. This study aims to investigate the effect of flashcard media displayed on the literacy window on students’ vocabulary mastery at SMP IT Al-Wahidiyah. The research employed a quantitative approach with a pre-experimental one-group pretest–posttest design involving 17 seventh-grade students. A vocabulary test consisting of 30 multiple-choice items was administered before and after six treatment sessions using flashcards on the literacy window. The results showed an increase in the mean score from 46.35 in the pretest to 64.35 in the posttest, with a significance value of 0.000 (<0.05), indicating a significant improvement in students’ vocabulary mastery. These findings suggest that the combination of flashcards and literacy windows provides repeated exposure that strengthens students’ memory and enhances vocabulary retention. This approach is therefore recommended as an effective strategy for improving vocabulary mastery among junior high school students.